El emprendimiento por necesidad, una ventana hacia el desarrollo de oportunidades de negocios - Pico Versoza, Lucía Magdalena (2017)
This study aims to analyze entrepreneurship by necessity, a situation faced by many individuals who, when engaging in an entrepreneurial venture, do not manage to obtain increasing returns, sometimes resulting in a failure of the business, but there is the possibility of recognizing market opportunities. Which, when identified in a timely manner, will create a window for the planning of strategies that will shape the entrepreneur towards positioning and business success.